Determining The Relationship Between Quality Control Programs And Sustainability Among Contractors in Saudi Arabia (Abstract) - Fadl Mohamed Fadl, Fathi (2013)
Kajian ini mensasarkan untuk mengkaji perkaitan diantara program kawalan kualiti dan kelestarian dikalangan kontraktor di Arab saudi.